PEMBELAJARAN BERBASIS KOMPUTER SARANA MULTIMEDIA DALAM PENGEMBANGAN PENDIDIKAN - MERENTEK, RISAL M. (JURNAL PENDIDIKAN DASAR, 2012)
Computer Assisted Instructions represents one of exploiting of e-learning in study. Usage of computer in study usualy can be utilized in two forms of study of that is Computer Assisted Instruction (CAI) and Computer Bassed Instruction (CBI). Both forms of this study model mengharus-kan every student to have interaction with computer peripheral and software programes, with basic difference in broadness of its(the function. As for study based on computer to more deepened by that is CAI (Computer Assisted Instruction). Computer Assisted Instructions it is computer application as integral part in study system to learning process and teachs with aim to assist student in learning of can pass interaction pattern two directions through computer terminal want to also multi direction which is extended by through computer network (local good want to also global) as well as extended by the function through interface (interfacial) multimedia. Computer Assisted Instructions (CAI) direct related with exploiting of computer in (activity) study in and external of class, either individually or in group of. CAI can be interpreted as a form of study which places computer in role of teacher, where student with interaction directly with computer and control fully student hand so that enables student learns down alley and chooses matter (study) as according to its requirement.Key Words: Computer Assisted Instruction, Computer Bassed Instruction, Multimedia